Governance and The Persistence Of Oil-Driven Conflict In The Niger Delta Region Of NigeriaGovernance and The Persistence of Oil-Driven Conflict in The Niger Delta Region of Nigeria - Ariyo Andrew Tobi (Journal of Public Administration and Government, 2022)
Over the years, oil and gas resources have spawned a series of hostilities in the Niger Delta region of Nigeria. Apart from the disruption of oil production, they have heightened social tension and security challenges in the region. This study probed the hostilities to identify their causes and persistence and discuss how they could be mitigated. The study employed a qualitative research design and used data obtained from secondary sources. It found that, although oil wealth constitutes a large percentage of total revenue and foreign exchange to the Nigerian government, oil production has spawned a conflict of various magnitudes, which include those between the people of the region and the oil companies, those between the people and the government as well as inter and intra communal hostilities. This study linked the protracted oil resource driven conflict to the distortion of governance and mismanagement of oil and gas wealth, which have not addressed the grievances of the people of the region. It posited that the persistent conflict could be assuaged through a redefinition of governance which entails adherence to extant regulations on oil exploration to protect the environment, effective and judicious management of oil wealth and infrastructural development in the region. Others include creating jobs for the teeming youth and constant dialogue with the region's inhabitants.